Peran Pondok Pesantren dalam Mendorong Pertumbuhan Ekonomi Masyarakat: The Role of Islamic Boarding Schools in Encouraging Community Economic Growth - Cantik Tri Rahajeng (Yayasan Letiges Konsultan Sosial, 2026)
Amanatul Ummah Islamic Boarding School plays a significant role in driving the economic transformation of the Kembangbelor Village community, Pacet District, Mojokerto Regency. Before establishing the Islamic boarding school, the village faced a relatively high level of poverty, as most residents relied solely on the agricultural sector. The presence of the Islamic boarding school significantly contributed to accelerating the economic growth of its residents. In a theoretical framework, a role is a set of behaviours expected of individuals and institutions with a social position within the community. This study focuses on analysing the role of Amanatul Ummah Islamic Boarding School in improving the economy of Kembangbelor Village. The research method used was a qualitative case study approach in Kembangbelor Village. Data were collected through primary and secondary sources, then analysed using the Miles and Huberman data analysis model. The research findings indicate that Amanatul Ummah Islamic Boarding School contributes to job creation by involving the community as educators, security guards, cooks, cleaners, construction workers, and laundry services. Furthermore, the Islamic boarding school also opens business opportunities for residents by establishing kiosks, coffee shops, street vendors, lodging, and parking services. These various roles demonstrate that Amanatul Ummah Islamic Boarding School can empower the community to improve its economic situation. However, a more comprehensive and sustainable program is needed for optimal community empowerment.